Digital Literacy in Learning Media in the Vocational Education of Serving Dishes - Yeni Yulianti; Annis Kandriasari; Guspri Devi Artanti; Vina Dwiyanti (Jurnal Pendidikan Indonesia, 2023)
The strengthening of the education system launched by the government is a new literacy movement, namely digital literacy. Digital literacy in culinary vocational education is still lacking in system and integration. One of them is web processing to support the learning process that has not been maximized. Therefore this study aims to develop web-based digital literacy that can guide independent learning. The approach taken is through R&D of digital media through WIX with the ADDIE model. The subjects of this study were students of the Culinary Education study program. Descriptive data analysis techniques on alpha and beta testing. The results obtained by media experts were 93.64% and material experts were 95% in the "very decent" category. The gain value of 0.72 is in the range G> 0.7 which means an increase in knowledge before and after using digital media for web-based F&B service dishes with a high category. Thus the website product in the F&B service course is appropriate to be used as a form of learning innovation in supporting the 4.0 era. and a digital literacy-based education system, especially vocational education.